Employment Adjustment during the Global Crisis: Differences between State-Owned and Private Enterprises - Álmos Telegdy (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
This paper analyses the employment adjustment of state- and privately-owned companies before and during the global crisis. Using Hungarian data, it finds that the net job creation rate is similar across the two ownership types before the crisis, but during the crisis state-owned companies have a net job creation rate larger by 7 percentage points than private enterprises. The effect is caused both by a larger gross job creation rate and by a drop in job destruction associated with state ownership.
Keywords: F23; L25; L32; 330; Net job creation; Global crisis; State ownership; Hungary; Zweiter Arbeitsmarkt; Öffentliches Unternehmen; Privatwirtschaft; Wirtschaftskrise; Russland